2021
DOI: 10.58524/oler.v1i2.54
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning model with zoom breakout rooms application: Its impact on students’ scientific literacy

Abstract: This study aims to determine whether there is an effect of the PBL model assisted by the Zoom Breakout Rooms application on the scientific literacy abilities of the students in Grade X SMA Qur’an Darul Fattah Bandar Lampung on environmental change material. The design used in this study was a quasi-experimental design with a Pretest-Postest Non-equivalent (The Non-equivalent Control Group Design). The population of this study was all students of class X SMA Qur’an Darul Fattah Bandar Lampung for the academic y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…PBL-based digital worksheets direct students' attention to problem-solving. PBL-based learning significantly improves students' digital literacy skills (Priadi et al, 2021;Kashyap et al, 2023). Similar research findings are conducted by Yustina et al (2022), who discovered that PBL-based learning can improve students' digital literacy skills.…”
Section: Figure 3 Ocean Wavesmentioning
confidence: 99%
“…PBL-based digital worksheets direct students' attention to problem-solving. PBL-based learning significantly improves students' digital literacy skills (Priadi et al, 2021;Kashyap et al, 2023). Similar research findings are conducted by Yustina et al (2022), who discovered that PBL-based learning can improve students' digital literacy skills.…”
Section: Figure 3 Ocean Wavesmentioning
confidence: 99%
“…In online learning, education takes place on the Internet using Information and Communication Technology (ICT) tools and platforms such as videos, audios text, Zoom, Google Classroom, and Learning Management Systems (LMS) (Juhji et al, 2022;Priadi et al, 2021). Asynchronous and synchronous tools are used to communicate with students in online courses.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has significantly impacted education, with many schools and universities shifting to remote or online learning. This has presented challenges for students and educators, including difficulties with technology and internet access and a need for more interaction and engagement than in-person learning (Almaiah et al, 2020;Priadi et al, 2021;Yuningsih et al, 2021. However, many institutions have also implemented innovative solutions and adapted to the new environment. Some research has suggested that online learning can be as effective as in-person instruction (Adedoyin & Soykan, 2020).…”
Section: Introductionmentioning
confidence: 99%